Impactos do Diabetes Mellitus Tipo 2 na qualidade de vida da população amazônica: a importância da atuação da equipe multiprofissional - TORRES, Luana Cristina Fiel (Universidade Federal do Pará, 2025)
In the diagnosis of Type 2 Diabetes Mellitus (T2DM), the individual produces insufficient insulin, and the group most affected by this disease are people over 30 years old, obese or overweight, caused by the result of the relationship between hereditary and environmental factors and/or associated with population aging and an unhealthy lifestyle, with low frequency of physical activity, obesity and inadequate diet. T2DM is a chronic disease associated with high morbidity and mortality and impaired Quality of Life (QoL) and represents a public health problem due to its increased incidence and prevalence. The objective of this research was to present the possible association between QoL and T2DM and the evidence regarding the impacts of factors such as the performance of the multidisciplinary team. For this purpose, a cross-sectional study was carried out with 30 patients, in which two scales were applied and analyzed: the “B-PAID” and the WHO Quality of Life (WHOQOL – Brief), from October 2023 to June 2024, at the Endocrinology outpatient clinic of the João de Barros Barreto University Hospital - Belém - PA, in addition to the sociodemographic survey such as gender, age group, race/ethnicity, municipality, team and complications of DM2. Through this study, a profile of participants was obtained, these being people of both genders, aged between 50-69 years, brown, who lived in Belém, had greater monitoring by the endocrinologist and the nurse and had as main complications hypertension and dyslipidemia. The results found after analyzing the climbs were that this participant profile had as risk factors their QoL, economic variables, physical pain as an impediment to performing their routine activities, the feeling of not having clear goals for their treatment; not knowing how to deal with complications resulting from DM2 and a future of possible worsening of these. Subsequently, the participants were divided into two groups: “participants accompanied by up to two professionals” and “participants accompanied by three or more professionals” and the result obtained was that the latter group had the possibility of greater success in their treatment and better quality of life.